DEVELOPMENT AND IMPLEMENTATION OF INTEGRATED SOLUTIONS BASED ON IIOT FOR THE INTELLIGENT PACKAGING - Oleksandr Gavva; Liudmyla Kryvoplias Volodina; Oleksandr Savchuk; Dumitru Mnerie (Nonconventional Technologies Review, 2025)
The synthesis of mechatronic modules combining heterogeneous physical principles is an urgent task of modern engineering. The study focuses on the development and implementation of integrated solutions based on IIoT to optimize the operation of robotic manipulators intended for product packaging. A methodology for processing data at the level of IIoT endpoints is proposed to minimize the amount of transmitted information and increase the efficiency of the system. To solve the tasks, an unconventional approach was taken, identifying certain methods of mathematical modeling and optimization. Models and simulation methods were developed for processing information on the endpoints of IІoT devices related to packaging equipment, aiming to reduce the amount of data transmitted and stored in IIoT systems. In the paper, based on the research results, a study was conducted on the influences of various parameters on the accuracy of dosing and recommendations were developed for optimizing the process.